Essentials of clinical pathology - Kawathalkar, Shirish M. (Jaypee Brothers Medical Pub., 2010)
Essentials of Clinical Pathology explains the basic fundamentals of clinical chemistry, laboratory tests in diagnosis and management of diseases. It is mainly intended for second MBBS students and postgraduate residents in pathology. It will also be an essential reading for students of medical laboratory technology. Its main strengths are easy readability, scientific basis, incorporation of most recent concepts, and clinical relevance. Discussion of laboratory tests is preceded, where required, by basic information on anatomy, physiology, and a concise outline of relevant diseases to facilitate understanding.